Neutralization of inhibitory antibodies and restoration of therapeutic ADAMTS‐13 activity levels in inhibitor‐treated rats by the use of defined doses of recombinant ADAMTS‐13. (12th October 2015) - Plaimauer, B.; Schiviz, A.; Kaufmann, S.; Höllriegl, W.; Rottensteiner, H.; Scheiflinger, F.
Summary: Background: Acquired thrombotic thrombocytopenic purpura (TTP) is caused by an autoantibody‐mediated deficiency of the von Willebrand factor‐cleaving protease ADAMTS‐13. Acute episodes of the disease are treated with a combination of immunosuppression and repeated cycles of plasma exchange to remove anti‐ADAMTS‐13 autoantibodies and, at the same time, replenish functional ADAMTS‐13. Although this is often effective, the mortality rate has remained between 10% and 20%, highlighting the need for safer treatment options. Objectives: We previously showed that, in vitro, human recombinant ADAMTS‐13 (rADAMTS‐13) is able to override neutralizing antibodies and restore ADAMTS‐13 activity in plasma from patients with acquired TTP. In the present study, we assessed the in vivo feasibility of this strategy by using a rat model. Methods: Wild‐type rats were adjusted to an ADAMTS‐13 inhibitor (inhibitor) titer of ~ 10 BU mL −1 with goat anti‐ADAMTS‐13 IgG, and treated with increasing doses of rADAMTS‐13. Blood samples were drawn and analyzed for ADAMTS‐13‐specific parameters, including FRETS‐VWF73 activity, inhibitor, and ADAMTS‐13‐specific immune complexes (ICs). The pharmacokinetics of ADAMTS‐13 activity and inhibitors were evaluated. Results: Administration of inhibitor titer‐adjusted doses of rADAMTS‐13 to inhibitor‐treated rats predictably restored activity. Inhibitors were readily neutralized through formation of ADAMTS‐13‐specific ICs, which were cleared at a higher rate than the free inhibitor. Surplus protease was enzymatically active in plasma, and showed similar pharmacokinetics to ADAMTS‐13 in not inhibitor‐treated rats. Conclusions: Defined doses of rADAMTS‐13 neutralized circulating anti‐ADAMTS‐13 antibodies and enabled reconstitution of ADAMTS‐13 activity in plasma in our model, indicating that the protease may be a promising candidate for further exploration in treating acute episodes of acquired TTP.